Time Factor for E-KTP Service Through POS KETANMU at the Population and Civil Registration Office : Faktor Waktu Pelayanan E-KTP Melalui POS KETANMU Di Dinas Kependudukan dan Pencatatan Sipil - Silfiatin, Lina; Choiriyah, Ilmi Usrotin (Indonesian Journal of Public Policy Review, 2023)
The government of the Population and Civil Registration Service of the Mojokerto Regency in implementing E-KTP services through the online service without meeting systems (POS KETANMU) must have a predetermined goal or target. To support the realization of E-KTP services in accordance with standard operating procedures, it must have the right time factor so that this E-KTP services can be carried out quickly and precisely. This study aims to describe the condition of an object of research, namely the E-KTP service through POS KETANMU as it is and based on existing facts. This research method uses a qualitative method with a descriptive approach. The results of the study show that the time factor has provided services to the community and has not received a good response from the community. The public is enthusiastic to hear about the E-KTP service through this online system. However, the implementation process has not yet reached the predetermined time factor. This is due to the lack of orderly service providers in responding to request for public services.